Culture pedagogies and pedagogical propositions: Artistic experiences for children (Olhar de Professor, 2021)
This article aims to analyze artistic experiments with children from four propositions developed in different educational spaces in the city of Santa Maria - RS. The educational perspective of visual culture by Raimundo Martins and Irene Tourinho (2011) intertwined with the reflections of Susana Rangel Vieira da Cunha (2010, 2014, 2017) and Bricolage (KINCHELOE, J; BERRY, K, 2007) construct the theoretical-methodological field that seeks to problematize children's artistic productions concerning their visual repertoires. In this way, the present study approaches ways of proposing and reflecting on the experience of art-making with children, stimulating their protagonism based on the pedagogical power of the visual narratives from their imaginations. The results presented, entangled by the theoretical framework, offer clues to continue investigating and proposing the field of cultural pedagogies as an alternative to pedagogical practices.
Keywords: Culture Pedagogies. Pedagogical Propositions. Artistic Experiments.